Ergodicity of Stochastic Burgers’ System with Dissipative Term - Zhou, Guoli; Guo, Boling; Huang, Daiwen; Han, Yongqian (Abstract and Applied Analysis, 2013)
A 2-dimensional stochastic Burgers equation with dissipative termperturbed by Wiener noise is considered. The aim is to prove the well-posedness,existence, and uniqueness of invariant measure as well as stronglaw of large numbers and convergence to equilibrium.